The legend of korra: turf wars omnibus ebook - DiMartino, Michael Dante (The Legend of Korra: Turf Wars (2017)., 2022)
After a refreshing sojourn in the Spirit World, Korra and Asami return to Republic City but find nothing but political hijinks and human vs. spirit conflict! A developer plans to turn the new spirit portal into an amusement park, endangering relations with the spirits. At the city's edge, Zhu Li enlists everyone she can to aid the evacuees who have relocated there. Meanwhile, the Triple Threats' ruthless new leader, Tokuga, is determined to unite the other triads under his rule. In order to get through it all, Korra and Asami vow to look out for each other—but first, they've got to get better at being a team! Collects Turf Wars parts 1-3.